Plasminogen Activator Inhibitor-1 (PAI-1) 4G/5G Promoter Polymorphism and Levels in Subjects with Cerebrovascular Disease - Catto, Andrew J; Carter, Angela M; Stickland, Max; Bamford, John M; Davies, J Andrew; Grant, Peter J (Thrombosis and Haemostasis, 1997)
The exact role of the fibrinolytic system in the pathogenesis of stroke remains to be established. Elevated circulating levels of plasminogen activator inhibitor-1, the principle inactivator of the fibrinolytic system, have been related to the development of myocardial infarction. There is evidence that a polymorphism in the promoter region of the PAI-1 gene is associated with circulating PAI-1 levels.We studied a common single nucleotide insertion/deletion (4G/5G) polymorphism by PCR in 558 patients with stroke, the pathological type of which was established by cranial computed tomography, and in 172 controls. 4G/5G genotype and PAI-1 activity were investigated in relation to 1) stroke type and 2) mortality occurring within four weeks, three months and six months of the stroke.No difference in genotype frequency was observed when all cases of stroke were compared with controls nor between the clinically determined subtypes of cerebral infarction. PAI-1 activity was significantly higher in patients with stroke (n = 245) both at presentation (11.6 U/ml) and after three months (11.8 U/ml), in paired samples, than in control subjects (8.8 U/ml, p <0.0001). Thirty-seven (6.2%), 86 (14.5%) and 122 (20.5%) patients had died within one, three and six months of admission, respectively. PAI-1 activity was independently associated with all-cause mortality at one and three months after stroke (p = 0.02 and p = 0.03 respectively), but not after six months.In this population the 4G/5G promoter polymorphism is not associated with an increased risk of stroke. PAI-1 levels were elevated at the time of acute stroke which persisted after three months. PAI-1 level but not genotype was associated with early mortality following stroke.